The Assessment of Seawater Intrusion on The North Coast of Aceh Besar: A Surface Water and Well Water Study - Muhammad Irham; Ilhamsyah Putra; Irwansyah Irwansyah; Ichsan Setiawan; Ichsan Rusdi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: Groundwater that is used excessively in coastal areas will have an impact on the entry of salt water into groundwater so that groundwater becomes salty, a process called seawater intrusion. This study aims to determine the spatial distribution of seawater intrusion on the north coast of Aceh Besar. The method used in this study is a random and purposive sampling method on resident well water and surface water in both high and low tide conditions. The collected data was visualized using ArcGIS in the form of a spatial map. The results of the study show that the north coast of Aceh Besar in the eastern part has experienced seawater intrusion, while in the west it has the potential for seawater intrusion. Meanwhile, the salinity level for well water used daily is brackish, so it cannot be used for drinking water and other hygiene needs. The result of the correlation test between salinity and distance shows that salinity is not influenced by distance with a value of 4.17%. However, it is influenced by other factors such as land subsidence due to aquaculture activities and the nature of the rocks that make up the aquifer with a value of 95.83%.Abstrak: Air tanah yang dimanfaatkan secara berlebihan di daerah pesisir akan berdampak pada masuknya air asin ke dalam air tanah sehingga air tanah menjadi asin yang disebut dengan intrusi air laut. Penelitian ini bertujuan untuk mengetahui sebaran spasial intrusi air laut di pantai utara Aceh Besar. Metode yang digunakan dalam penelitian ini adalah metode random dan purposive sampling pada air sumur penduduk dan air permukaan baik pada kondisi pasang maupun surut. Data yang terkumpul divisualisasikan menggunakan ArcGIS dalam bentuk peta spasial. Hasil kajian menunjukkan bahwa pantai utara Aceh Besar di bagian timur telah mengalami intrusi air laut, sedangkan di bagian barat berpotensi terjadi intrusi air laut. Sementara tingkat salinitas untuk air sumur yang digunakan sehari-hari adalah payau sehingga tidak dapat digunakan untuk air minum dan kebutuhan kebersihan lainnya. Hasil uji korelasi antara salinitas dan jarak menunjukkan bahwa salinitas tidak dipengaruhi oleh jarak dengan nilai 4,17%, namun dipengaruhi oleh faktor lain seperti penurunan muka tanah akibat kegiatan budidaya dan sifat batuan penyusun akuifer dengan nilai 95,83%.